Pengembangan dan Penerapan Kurikulum Biologi Kontekstual untuk Konservasi Sumber Daya Alam dan Pembelajaran Berorientasi SDGs - Fahmie Firmansyah; Saprolla Rollie Cale Deporos; Fazri Yulianto; Adnin Mutiara (Biosfer: Jurnal Pendidikan Biologi, 2026)
This study aims to design, develop, and test a contextual biology curriculum focused on natural resource conservation, aligned with Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 15 (Life on Land). The Research and Development (R&D) method, using a modified 4D model (define, design, develop, disseminate), was employed to create a practical and effective curriculum. The Define stage identified gaps in the existing high school biology curriculum, particularly the lack of integration of local environmental issues and SDGs. The Design stage resulted in the development of syllabi, lesson plans, modules, and conservation-based teaching materials, systematically linking biological concepts such as ecosystems, biodiversity, and the life cycle of organisms with local conservation topics. Project-based learning and field activities were incorporated to enhance student engagement and promote environmental responsibility. The Develop stage involved expert validation and classroom trials, confirming the feasibility and effectiveness of the curriculum. The results showed significant improvement in students’ understanding of biological concepts and conservation, as well as positive changes in their pro-environmental attitudes and behaviors. This research provides a new framework for integrating sustainability into the biology curriculum, addressing local and global environmental challenges. The implications of this study are significant for curriculum development, offering a model for educators to foster environmental literacy and contribute to the achievement of the SDGs through practical, real-world learning experiences.